2013
DOI: 10.1017/s1751731113001286
|View full text |Cite
|
Sign up to set email alerts
|

Differences in rate of ruminal hydrogenation of C18 fatty acids in clover and ryegrass

Abstract: Biohydrogenation of C18 fatty acids in the rumen of cows, from polyunsaturated and monounsaturated to saturated fatty acids, is lower on clover than on grass-based diets, which might result in increased levels of polyunsaturated fatty acids in the milk from clover-based diets affecting its nutritional properties. The effect of forage type on ruminal hydrogenation was investigated by in vitro incubation of feed samples in rumen fluid. Silages of red clover, white clover and perennial ryegrass harvested in sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…In winter, grass/clover silage commonly used in ORG systems when pasture is not available, has been found to increase ALNA concentrations when compared with grass or grass/maize silage (Dewhurst, Fisher, Tweed, & Wilkins, 2003;Wiking, Theil, Nielsen, & Sorensen, 2010), commonly used in the CON systems. This may be explained by the slower DM degradation (Dewhurst, Evans, Scollan, Moorby, Merry, & Wilkins, 2003) and rates of RBH of clover compared with grass (Lejonklev, Storm, Larsen, Mortensen, & Weisbjerg, 2013), which may increase rumen passage rates, reduce RBH of ALNA, and eventually increase transfer rates of dietary ALNA to milk. In humans and animals, including cattle, ALNA is used as substrate for the synthesis of EPA and DPA by various enzymes, including elongases, Δ 5 -desaturase and Δ 6 -desaturase ( Barcelo-Goblijn, et al, 2009).…”
Section: Organic Milkmentioning
confidence: 99%
“…In winter, grass/clover silage commonly used in ORG systems when pasture is not available, has been found to increase ALNA concentrations when compared with grass or grass/maize silage (Dewhurst, Fisher, Tweed, & Wilkins, 2003;Wiking, Theil, Nielsen, & Sorensen, 2010), commonly used in the CON systems. This may be explained by the slower DM degradation (Dewhurst, Evans, Scollan, Moorby, Merry, & Wilkins, 2003) and rates of RBH of clover compared with grass (Lejonklev, Storm, Larsen, Mortensen, & Weisbjerg, 2013), which may increase rumen passage rates, reduce RBH of ALNA, and eventually increase transfer rates of dietary ALNA to milk. In humans and animals, including cattle, ALNA is used as substrate for the synthesis of EPA and DPA by various enzymes, including elongases, Δ 5 -desaturase and Δ 6 -desaturase ( Barcelo-Goblijn, et al, 2009).…”
Section: Organic Milkmentioning
confidence: 99%
“…Milk from both OM and CL systems showed more desirable FA profiles than CH milk, but there were also differences between these two systems. For example, CL milk was higher in VA and RA compared with OM milk, possibly reflecting the higher pasture intake on CL farms (Butler et al 2008) exacerbated by lower rates of hydrogenation (less VA production) associated with clover inclusion in the OM swards (Dewhurst et al 2009;Lee et al 2009;Lejonklev et al 2013). This finding is particularly interesting because Stergiadis et al (2012) reported that raising pasture intake from 200 to 370 g/kg of DMI throughout the year did not have a significant impact on VA and RA contents of milk but a similar increase (albeit from a much higher baseline) in pasture intake in the present study (700 g/kg DMI for OM v. 840 g/kg DMI on CL farms) did significantly raise milk VA and RA concentrations by 21 and 28%, respectively.…”
Section: Effect On Fatty Acid Compositionmentioning
confidence: 99%
“…Extensive research with dietary n-3 fatty acid sources has focused on changing milk fatty acid composition (Shingfield et al, 2005;Lejonkleva et al, 2013;Nudda et al, 2013;Gallardo et al, 2014), disregarding the effect of n-3 fatty acids on the immune system or oxidative stress in dairy cows. The aim of this research was to determine the influence of dietary replacement of n-6 with n-3 polyunsaturated fatty acids (PUFA) on cellular immunity and oxidative stress in the transition period of dairy cows.…”
Section: Introductionmentioning
confidence: 99%